PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI PERSOALAAN BULLYING DI SEKOLAH MENENGAH PERTAMA (SMP) - Ernawati, Ernawati (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2022)
This study examines the role of Islamic Religious Education (PAI) teachers to overcome problems related to bullying that occurs in Indonesia. Descriptive research is the research used by researchers in this study. Researchers describe facts, data, and information obtained from literature studies such as books, and journals to research results related to the topic of research. In this study, it is explained that bullying is a vital problem and must be resolved immediately in the realm of education in Indonesia. This is because there are no positive benefits derived from this bullying behavior. From this research, it is also known that there are several types, factors, and impacts or effects felt by students as a result of bullying behavior carried out. These three aspects can be a guide for teachers to analyze and formulate strategies to solve this problem. One of the subject teachers who have a big role is the PAI teacher at school considering that this subject teaches students to have good morals, personality, and character by Islamic law. In making it happen, PAI teachers must make various efforts in the process, such as teachers need to include religious values ​​in the bullying that occurs so that students understand and know that this action is wrong and very detrimental. In addition, teachers also need to provide role models in cleaning and behaving, teachers can also provide Islamic guidance and counseling to students in need. Finally, there is a need for cooperation between parties to overcome this problem, both from the school and parents as the family to provide monitoring and examples to continue to implement the values ​​of goodness in Islam in the daily lives of students.